1988
DOI: 10.1901/jeab.1988.50-457
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Component Duration on Multiple‐schedule Performance in Closed and Open Economies

Abstract: Pigeons responded on multiple variable-interval variable-interval schedules of reinforcement in an open and a closed economy. Equal duration components were increased in duration while the component rates of reinforcement were held constant, the component schedules were reversed, and component duration was decreased. In the open economy, daily sessions were limited to 1 hr, and subjects were maintained at 80% of their free-feeding weights through supplemental feeding when necessary in their home cages. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…These variables covaried with changes in economic context and constitute a potential confound in any study that uses as an independent variable the type of nominal economy differences presented here. Similar problems associated with a withinsubjects comparison of the effects of closed versus open economies have been discussed with respect to successive schedule performance (LaFiette & Fantino, 1988). Because the terminal links of concurrent-chains schedules may be viewed as successively presented schedules (see Wardlaw & Davison, 1974), and the effects of these variables (those related to open and closed economies) on responding in successive schedules are well documented (Elliffe & Davison, 1985;Herrnstein & Loveland, 1974), there is the possibility that these factors might have interacted to produce the present results.…”
Section: Resultsmentioning
confidence: 55%
“…These variables covaried with changes in economic context and constitute a potential confound in any study that uses as an independent variable the type of nominal economy differences presented here. Similar problems associated with a withinsubjects comparison of the effects of closed versus open economies have been discussed with respect to successive schedule performance (LaFiette & Fantino, 1988). Because the terminal links of concurrent-chains schedules may be viewed as successively presented schedules (see Wardlaw & Davison, 1974), and the effects of these variables (those related to open and closed economies) on responding in successive schedules are well documented (Elliffe & Davison, 1985;Herrnstein & Loveland, 1974), there is the possibility that these factors might have interacted to produce the present results.…”
Section: Resultsmentioning
confidence: 55%
“…Such a situation is called a closed economy (Hursh, 1980(Hursh, , 1984, in contrast with the more commonly arranged open economy, in which subjects are maintained at a constant level of food deprivation by supplementary food given outside the experimental session. Elliffe LaFiette and Fantino (1988) have also reported overmatching in closed-economy multiple schedules, at least at component durations similar to those used by Elliffe and Davison. One variable known to affect sensitivity in multiple schedules is the level of deprivation of the scheduled reinforcer. Both Herrnstein and Loveland (1974) and Charman and Davison (1983), using pigeons responding for food reinforcers on open-economy multiple VI schedules, found that sensitivity approached strict matching (a = 1.0) as subjects were made less food deprived.…”
mentioning
confidence: 56%
“…Elliffe and Davison (1985) reported consistent overmatching (a > 1.0) in an experiment in which pigeons received their total intake of food as reinforcers for responding on multiple schedules available 24 hr per day. Such a situation is called a closed economy (Hursh, 1980(Hursh, , 1984 Fantino (1988) have also reported overmatching in closed-economy multiple schedules, at least at component durations similar to those used by Elliffe and Davison. One variable known to affect sensitivity in multiple schedules is the level of deprivation of the scheduled reinforcer. Both Herrnstein and Loveland (1974) and Charman and Davison (1983), using pigeons responding for food reinforcers on open-economy multiple VI schedules, found that sensitivity approached strict matching (a = 1.0) as subjects were made less food deprived.…”
mentioning
confidence: 89%
See 2 more Smart Citations